2021
DOI: 10.2106/jbjs.rvw.21.00069
|View full text |Cite
|
Sign up to set email alerts
|

Management of de Quervain Tenosynovitis

Abstract: Most cases of de Quervain tenosynovitis can be managed with nonoperative measures, and the mainstay of treatment is corticosteroid injection (CSI). The use of ultrasound may improve the accuracy of injections and can help to identify and localize injections to separate subcompartments.For patients who are in the third trimester of pregnancy or breastfeeding, there is no contraindication to CSI as studies have shown that it can provide optimal symptomatic relief to the mother without impacting the baby.When non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Corticosteroid injection is a commonly implemented intervention. While previous studies suggest that corticosteroid injection may be effective in reducing de Quervain’s syndrome symptoms, 61 recurrence rates as high as 48% have been reported. 62 The literature, supported by the findings in this study, suggests that a proportion of people with de Quervain’s syndrome elect to trial conservative interventions before progressing to more invasive interventions of injection or surgery.…”
Section: Discussionmentioning
confidence: 91%
“…Corticosteroid injection is a commonly implemented intervention. While previous studies suggest that corticosteroid injection may be effective in reducing de Quervain’s syndrome symptoms, 61 recurrence rates as high as 48% have been reported. 62 The literature, supported by the findings in this study, suggests that a proportion of people with de Quervain’s syndrome elect to trial conservative interventions before progressing to more invasive interventions of injection or surgery.…”
Section: Discussionmentioning
confidence: 91%
“…Nonoperative first-line treatment for de Quervain tenosynovitis consists of nonsteroidal anti-inflammatory drugs, thumb spica immobilization (splint immobilizing the wrist and thumb), or corticosteroid injection. Other nonoperative therapies include laser therapy, acupuncture, and placebo injection . A 2015 meta-analysis of 5 RCTs including 185 patients concluded that corticosteroids were associated with superior resolution of symptoms (84% vs 31%; RR, 2.59; 95% CI, 1.25 to 5.37; P = .05), pain relief (visual analog scale mean difference, −2.51; 95% CI, −3.11 to −1.9; P < .001), and functional improvement compared with that of control groups (splinting, placebo injection, and acupuncture) .…”
Section: Methodsmentioning
confidence: 99%
“…When nonoperative treatment fails, operative treatment consists of releasing the first dorsal extensor compartment through open, endoscopic, or percutaneous approaches. Efficacy of open release is largely based on retrospective case series, with success rates of approximately 91% based on symptom relief in a case series of 43 patients . In an RCT of 52 patients with de Quervain tenosynovitis, compared with open release, endoscopic release of the first dorsal compartment reduced transient injuries to the radial sensory nerve (11% vs 36%; P = .03) and attained earlier symptom relief (mean visual analog scale pain score at 12 weeks [range of no pain, 0 to severe pain, 10], 2.7 vs 3.8; P = .01) and greater satisfaction with the surgical scar (mean visual analog scale score [range of not satisfied, 0 to fully satisfied, 10], 8.0 vs 6.1; P < .001) than did open release …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Quervain's disease is a common stenosing tenosynovitis that affects tendons in the first extensor compartment as a degenerative condition. 1 Severe pain and limitation of motion around the radial sides of the wrist and thumb restricts daily life activities, and the symptoms can sometimes persist for quite a long time. First-line conservative treatment consists of rest, activity modification, and oral analgesic or nonsteroidal anti-inflammatory agent administration.…”
Section: Introductionmentioning
confidence: 99%